Mediation as a practical tool for conflict resolution within workplaces in Iceland - Helga Kristín Ingólfsdóttir 1996- (2022)
Employees’ different personalities and ideas can lead to workplace conflicts that can be detrimental to businesses. To prevent them from escalating into larger ones, it is critical to address them adequately. The utilization of mediation’s methodology within workplaces has been gradual over the years because businesses find it efficient, flexible, and time- and costeffective conflict resolution. Thus, the current study’s hypothesis stated that mediation would be a practical tool for conflict resolution within workplaces in Iceland. This was examined with qualitative interviews based on a semi-structured frame of questions to answer further whether and how mediation can be applied within workplaces in Iceland. The study’s participants were 11 individuals that worked in various workplaces in Iceland. The selection criteria for participants were that they had attended a mediation course. The results indicated that mediation is a practical tool for conflict resolution within workplaces in Iceland. Further, participants found that a mediation course impacted their previous working methods, they saw more benefits than drawbacks in utilizing mediation, and participants had a vision of how to enhance mediation in Iceland in the future. Therefore, businesses in Iceland should unite behind mediation and encourage healthy communication among employees to ensure long-term business success. Keywords: conflict, conflict resolution, mediation, workplace Persónuleiki, ólíkar hugmyndir og upplifanir starfsfólks geta leitt til ágreinings á vinnustöðum sem getur verið skaðlegur fyrirtækjum. Til að koma í veg fyrir að ágreiningur stigmagnist er mikilvægt að leysa hann á réttan hátt. Notkun aðferðafræði sáttamiðlunar á vinnustöðum hefur aukist síðustu ár þar sem fyrirtækjum þykir sú aðferð skilvirk, sveigjanleg, skjót og hagkvæm lausn á ágreiningsmálum. Tilgáta rannsóknarinnar var þar með að sáttamiðlun er hagnýtt tól við lausn ágreiningsmála innan vinnustaða á Íslandi. Þetta var rannsakað með eigindlegum viðtölum sem byggðu á ...